Selective halide ion binding templation effect for a quadruple-stranded-helicate enabling the activation of C–Br bonds - Fu, Lei; Liu, Yang; Jiang, Zhiyuan; Zhang, Zhe; Bai, Qixia; Yu-Qing, Li; Chen, Zhi; Li, Xiaopeng; Wang, Pingshan; Wu, Tun (Organic chemistry frontiers an international journal of organic chemistry, 2024)
Here, we report the investigation of the mechanism of an anion-induced templation effect, in which nucleophilic anions serving as a ligand competitor destroy the partial coordination bonds of a library of metallo-macrocycles and form quadruple-stranded helicates with a vacant cavity. Due to its shape and size complementarity, the quadruple-stranded helicate can encapsulate spherical halide ions with moderate binding strength and specific selectivity. Through the halophilic templation effect, it is capable of binding and stabilizing bromide within the central cavity of the quadruple-stranded helicate, which has been exploited to promote C–Br bond cleavage. The dibenzhydryl carbocation (Ph2CH+) generated by the templation effect is an ideal electrophile that can react with various nucleophiles. Therefore, the library can efficiently catalyze a series of organic reactions including hydrolysis, alcoholysis, Ritter reaction and Friedel–Crafts benzylation of arenes and heteroarenes.